"My life isn't my life, it's the systems": A qualitative exploration of women's experiences of day‐to‐day restrictive practices as inpatients. Issue 1 (18th July 2022) - Tully, Sarah Michelle; Bucci, Sandra; Berry, Katherine
Accessible summary: What is known on the subject?: Sometimes someone needs to be in hospital because they are struggling with their mental health and need some extra support but being in hospital can also be a difficult experience. There are a lot of restrictions in place in hospital, like locked doors, rules to follow and not much choice about what happens to you. Other research has found that these restrictions can feel difficult and stressful for people and so more research is needed about this. We wanted to know what being in hospital felt like for women in particular. What the paper adds to existing knowledge?: We interviewed women who were in hospital because of their mental health about what it was like for them in hospital. The women told us that they felt powerless while they were in hospital. They sometimes felt like they were being punished and this could affect their mood and could lead to them hurting themselves. They also said that they were not always listened to by staff, and they found it difficult being away from their family and friends while they were in hospital. The women also told us that being in hospital could sometimes help them to feel safe. What are the implications for practice?: Women should be looked after in hospital in a way that helps them to feel in control of what happens to them. They should be supported to be able to go outside the hospital on leave, to keep in touch with their family and friends, and they should be listened to by staff. A project called "safewards" has suggested some ways for helping to make hospital wards safer. They have suggested that everyone should be clear about what the rules are when they go into hospital and ways that staff could communicate more clearly with the people they are working with. Our research supports using these techniques. Abstract: Introduction: Inpatient care often involves restrictive interventions such as seclusion and restraint and restrictive practices that limit the person's freedom, rights and daily activities. Restrictive practice has not been the explicit focus in previous research; however, it often appears as an important theme, with participants identifying it can have a detrimental effect on their well‐being. More research specifically on this topic in an inpatient setting is, therefore, needed. Women might be particularly vulnerable to adverse effects of restrictive practices compared to men as women generally occupy less powerful positions in society and more often experience abuse. Aims: The study aimed to explore women's experiences of routine restrictive practices in mental health inpatient settings. Methods: Twenty‐two women who were currently inpatients on mental health wards were interviewed about their experiences of restrictive practices in hospital. Interviews were analysed using thematic analysis. Results: An overarching theme emerged of powerlessness. Four key sub‐themes were also identified: restrictions perceived as punitive, having no voice, impact of restrictions on relationships and restrictions providing safety and support. Discussion: Although restrictive practices were found to provide the women with a sense of safety, they were also found to impact upon the women's well‐being, leading to increases in self‐harm and over‐reliance on restrictions. Implications for practice: This research highlights the importance of gender‐informed inpatient services for women that foster independence, empowerment and allow women to have their voices heard. Safewards interventions such as clear mutual expectations and soft words could contribute to mitigating the impact of restrictive practices.